Genesis : the story of how everything began - Tonelli, Guido, 1950- (Farrar, Straus and Giroux, 2021)
"A breakout bestseller in Italy, now available for American readers for the first time, Genesis: The Story of How Everything Began is a short, humanistic tour of the origins of the universe, earth, and life-drawing on the latest discoveries in physics to explain the seven most significant moments in the creation of the cosmos"--